REVISITANDO LA DISCUSIÓN ENTRE AUGUSTO SALAZAR BONDY Y LEOPOLDO ZEA. LA FILOSOFÍA LATINOAMERICANA: EL LUGAR DE UN DIFERENDO. - Echeverría, Cristóbal Friz (Revista de Filosofía (00348236), 2019)
This paper aims the discussion between Augusto Salazar Bondy and Leopoldo Zea about lateinamerican philosophy, that takes place towards the end of the 1960s. The objective is to show that this discussion is the place of a differendum; that means, of conflict between dissimilar positions and representations, in some cases irreconcilable. As proposed, what is discussed in that controversy is the meaning of philosophy and the philosophical, in contexs of enunciation such Latin America. For this, we review some conceptual nuclei of the dispute, showing it as a current philosophical discussion.